2010
DOI: 10.1007/s11307-010-0331-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FLT-PET and FDG-PET for Visualization of Head and Neck Squamous Cell Cancers

Abstract: FLT-PET showed as high a sensitivity as FDG-PET for the detection of primary HNSCC lesions, although uptake of FLT was significantly lower than that of FDG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 17 publications
1
18
1
Order By: Relevance
“…Patients with HNSCC had better PFS and OS in this study, consistent with historic data [3,4,7]. In contrast to the current study, larger prior studies in patients with HNSCC and EC have correlated worse outcomes with higher baseline SUVmax [14,[23][24][25]. Similarly, larger prior studies suggest that higher TLG values correlated with worse oncologic outcomes [24][25][26][27].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Patients with HNSCC had better PFS and OS in this study, consistent with historic data [3,4,7]. In contrast to the current study, larger prior studies in patients with HNSCC and EC have correlated worse outcomes with higher baseline SUVmax [14,[23][24][25]. Similarly, larger prior studies suggest that higher TLG values correlated with worse oncologic outcomes [24][25][26][27].…”
Section: Discussionsupporting
confidence: 85%
“…Positron emission tomography (PET) with 2-deoxy-2-18F-fluoro-dglucose (FDG) and 3'-deoxy-3'-18F-fluorothymidine (FLT) tracers have been used in HNSCC to define extent of disease and assess response to treatment [10][11][12][13][14][15]. A series of EC patients scanned with FDG-PET before and after induction chemotherapy showed a doubling in two-year disease-free survival when the SUVmax declined by greater than 60% [16].…”
Section: Introductionmentioning
confidence: 99%
“…All primary tumors were identified but with a large range in tracer uptake; there emerged only a weak correlation between 18 F-FLT uptake and iododeoxyuridine staining intensity in oral cavity tumors. Hoshikawa et al [78] evaluated 43 patients with HNSCCs. The mean SUV for 18 F-FLT was significantly lower than that for 18 F-FDG and significantly higher in poorly than in well-differentiated tumors.…”
Section: Head and Neckmentioning
confidence: 99%
“…The intracellular trapping of 18 F-FLT is a function of the enzymatic activity of thymidine kinase 1, a key enzyme in DNA synthesis with high activity during the proliferative S phase of the cell cycle and low activity in the quiescent G0/G1 phase (9). Untreated head and neck squamous cell cancers are readily detectable with 18 F-FLT PET, with high tumor-to-background ratios, although the SUV with 18 F-FLT tends to be generally lower than with 18 F-FDG (10)(11)(12)(13)(14). Comparison studies of 18 F-FLT and 18 F-FDG by Hoshikawa et al showed similar detectability and false-positive rates in primary tumors and cervical nodal metastases for 18 F-FLT and 18 F-FDG (11,12).…”
mentioning
confidence: 99%
“…Untreated head and neck squamous cell cancers are readily detectable with 18 F-FLT PET, with high tumor-to-background ratios, although the SUV with 18 F-FLT tends to be generally lower than with 18 F-FDG (10)(11)(12)(13)(14). Comparison studies of 18 F-FLT and 18 F-FDG by Hoshikawa et al showed similar detectability and false-positive rates in primary tumors and cervical nodal metastases for 18 F-FLT and 18 F-FDG (11,12). The pretherapy staging of head and neck cancer with 18 F-FLT PET appears limited by the nontumoral uptake in reactive cervical nodes due to proliferation of reactive B-lymphocytes (15).…”
mentioning
confidence: 99%